Embedding bio-Fenton in a hybrid membrane biofilm reactor enhances the treatment of antibiotic-contaminated saline water - Wei Li; Ying-Lian Lan; Xu Zhang; Yi-Hao Luo; Yu-Xiang Zhao; Ju-Ying Lei; Yong-Di Liu; Bruce E. Rittmann (Water Research, 2026)

Prenatal exposure to indoor PM2.5 and children's cognitive performance at 4 years of age: an observational analysis from the UGAAR randomized controlled trial - Battsetseg Ulziikhuu; Enkhjargal Gombojav; Chimeglkham Banzrai; Sarangerel Batsukh; Enkhtuul Enkhtuya; Buyantushig Boldbaatar; David C. Bellinger; Bruce P. Lanphear; Lawrence C. McCandless; Xing Yu; Ryan W. Allen (Environmental Pollution, 2026)

Probabilistic seismic hazard assessment for Taiwan: Updates and improvements in TEM PSHA2025 - Jia-Cian Gao; Jo-Chen Kao; Chung-Han Chan; Ray Y. Chuang; Cheng-Hung Chen; J. Bruce H. Shyu; Kuo-En Ching; Yu Wang; Kuo-Fong Ma (Engineering Geology, 2026)

Quantifying late Quaternary slip on the northern Yangsan Fault, Korea: implications for segment-scale variability in slip rate on a slowly deforming intraplate fault system - Taehyung Kim; Tae-Ho Lee; Jin-Hyuck Choi; Yire Choi; Youngbeom Cheon; Namgwon Kim; Changwan Sun; Yu Wang; J. Bruce H. Shyu; Hoil Lee (Tectonophysics, 2026)

Enhancing Medicine Safety Through Patient Empowerment - Yihua Bruce Yu; Rutendo Kuwana (Pharmaceutical Research, 2026)

Microbial electrosynthesis of methane in an up-scaled zero-gap cell - Bin Bian; Xinrui Ma; Sen Li; Najiaowa Yu; Chenghan Xie; Wulin Yang; Bruce E. Logan (Water Research, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

High-throughput fingerprinting of hydrolysable tannins in wine and oak wood using in-source fragmentation on QTOF and QQQ platforms - Yanxin Lin; Bruce S. Pan; Robert (Qiang) Sui; Ping Yu; Misha T. Kwasniewski (Food Chemistry, 2026)

Dysregulation of the BRD2-FGF17 Signal Pathway Induces Abnormal Forebrain Development Associated with Schizophrenia - Xiao Yu; Jiacheng Du; Chenger Zhou; Yongheng Huang; Huijuan Li; Bruce M. Cohen; Sangmi Chung; Zhicheng Shao (Neuroscience Bulletin, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

PTUPB improves cognitive function in Alzheimer’s disease associated with enhancing cerebral vascular myogenic response and attenuating vascular remodeling - Gilbert C. Morgan; Andrew Gregory; Chengyun Tang; Sung Hee Hwang; Jane J. Border; Jing Xu; Yedan Liu; Shan Bai; Tae Jin Lee; Cameron Cantwell; David Bunn; Karen M. Wagner; et al. (GeroScience, 2026)

A dual-resolution acoustic-sensing robot for autonomous in-pipe inspection - Xiaoyu Sun; Yicheng Yu; Xudong Niu; Zhenshan Wang; Alexander R.K. Towlson; Kirill V. Horoshenkov; Anthony J. Croxford; Bruce W. Drinkwater (Tunnelling and Underground Space Technology, 2026)

Diamide insecticides impair honey bee queen reproduction and colony development - Yong Huang; Quan Gao; Qibao He; Jinjing Xiao; Qiongqiong Liu; Yuying Liu; Min Liao; Yanhong Shi; Tengfei Shi; Yancan Wu; Qing Yang; Linsheng Yu; et al. (Science Bulletin, 2026)

A standardized nontargeted metabolomics method for cross-laboratory comparison of food profiles - Melanie T. Odenkirk; Cole Michel; Katrina A. Doenges; Katrina L. Leaptrot; Stacy D. Sherrod; Jody C. May; Margaret L. Read; Jacqueline M. Chaparro; Nathan Montgomery; Sarah Brinkley; Arpana Vaniya; Susan B. Mitchell; et al. (Food Chemistry, 2025)

High-rate and energy-efficient microbial electrosynthesis of methane using 3D dual-layer cathodes - Najiaowa Yu; Bin Bian; Pascal E. Saikaly; Hong Zhang; Kun Guo; Bruce E. Logan (Chemical Engineering Journal, 2025)

Corrigendum to “Development of a comprehensive food glycomic database and its application: Associations between dietary carbohydrates and insulin resistance” [Food Chemistry 473 (2025) 142977] - Christopher Suarez; Shawn Ehlers Cheang; Jules A. Larke; Jiani Jiang; Cheng-Yu Charlie Weng; Aaron Stacy; Garret Couture; Ye Chen; Nikita P. Bacalzo; Jennifer T. Smilowitz; J. Bruce German; David A. Mills; et al. (Food Chemistry, 2025)

Advancing Pharmaceutical Security: Noninvasive Detection of Falsified Vaccines and Drugs Using wNMR - Marc B. Taraban; Katharine T. Briggs; Pratima Karki; Leonid Grunin; Y. Bruce Yu (Pharmaceutical Research, 2025)

Development of a comprehensive food glycomic database and its application: Associations between dietary carbohydrates and insulin resistance - Christopher Suarez; Shawn Ehlers Cheang; Jules A. Larke; Jiani Jiang; Cheng-Yu Charlie Weng; Aaron Stacy; Garret Couture; Ye Chen; Nikita P. Bacalzo; Jennifer T. Smilowitz; J. Bruce German; David A. Mills; et al. (Food Chemistry, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Divalent site doping of NiFe-layered double hydroxide anode catalysts for enhanced anion-exchange membrane water electrolysis - Jun-Xi Wu; Yu Mao; Yongfang Zhou; Zihe Wang; Shanghai Wei; Bruce C.C. Cowie; Aaron T. Marshall; Ziyun Wang; Geoffrey I.N. Waterhouse (Chemical Engineering Journal, 2025)

Inhibition of soluble epoxide hydrolase ameliorates cerebral blood flow autoregulation and cognition in alzheimer's disease and diabetes-related dementia rat models - Chengyun Tang; Jane J. Border; Huawei Zhang; Andrew Gregory; Shan Bai; Xing Fang; Yedan Liu; Shaoxun Wang; Sung Hee Hwang; Wenjun Gao; Gilbert C. Morgan; Jhania Smith; et al. (GeroScience, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

A new strategy to generate nanobodies for the coumaphos based on the synthesized nanobody libraries - Ruyu Fang; Yingxue Li; Fei Liu; Yifan Liang; Yu Wang; Guohua Zhong; Zhenlin Xu; Bruce D. Hammock; Hong Wang (Food Chemistry, 2024)

Using a non-precious metal catalyst for long-term enhancement of methane production in a zero-gap microbial electrosynthesis cell - Bin Bian; Najiaowa Yu; Amir Akbari; Le Shi; Xuechen Zhou; Chenghan Xie; Pascal E. Saikaly; Bruce E. Logan (Water Research, 2024)

Fabrication of a label-free electrochemical immunosensor by functionalized nanofiber membrane for the ultrasensitive detection of quinalphos - Jian-cheng Hu; Peng Wen; Yu Wang; Jin-yi Yang; Zhi-li Xiao; Zhen-lin Xu; Yu-dong Shen; Hong Wang; Bruce D. Hammock (Food Control, 2024)

Advancing Li3VO4 as a high-performance anode material for use in lithium-ion batteries and lithium-ion capacitors - Yu-Sheng Hsiao; Jen-Hsien Huang; Lin-Yang Weng; Ta-Hung Cheng; Han-Hsin Chiang; Cheng-Zhang Lu; Huei-Chu Weng; Lars Thomsen; Bruce Cowie; Wei Kong Pang; Yu-Ching Huang (Chemical Engineering Journal, 2024)

Deconjugation potentials of natural estrogen conjugates in sewage and wastewater treatment plant: New insights from model prediction and on-site investigations - Jun Zhang; Ze-hua Liu; Jia-le Wu; Yu-ting Ding; Qing-guang Ma; Waseem Hayat; Yun Liu; Peng-jie Wang; Zhi Dang; Bruce Rittmann (Science of The Total Environment, 2024)

Intraspecific leaf trait variation mediates edge effects on litter decomposition rate in fragmented forests - Shilu Zheng; Mingjian Yu; Bruce L. Webber; Raphael K. Didham (Ecology, 2024)
There is strong trait dependence in species‐level responses to environmental change and their cascading effects on ecosystem functioning. However, there is little understanding of whether intraspecific trait variation (ITV) can also be an important mechanism mediating environmental effects on ecosystem functioning. This is surprising, given that global change processes such as habitat fragmentation and the creation of forest edges drive strong trait shifts within species. On 20 islands in the Thousand Island Lake, China, we quantified intraspecific leaf trait shifts of a widely distributed shrub species, Vaccinium carlesii , in response to habitat fragmentation. Using a reciprocal transplant decomposition experiment between forest edge and interior on 11 islands with varying areas, we disentangled the relative effects of intraspecific leaf trait variation versus altered environmental conditions on leaf decomposition rates in forest fragments. We found strong intraspecific variation in leaf traits in response to edge effects, with a shift toward recalcitrant leaves with low specific leaf area and high leaf dry matter content from forest interior to the edge. Using structural equation modeling, we showed that such intraspecific leaf trait response to habitat fragmentation had translated into significant plant afterlife effects on leaf decomposition, leading to decreased leaf decomposition rates from the forest interior to the edge. Importantly, the effects of intraspecific leaf trait variation were additive to and stronger than the effects from local environmental changes due to edge effects and habitat loss. Our experiment provides the first quantitative study showing that intraspecific leaf trait response to edge effects is an important driver of the decrease in leaf decomposition rate in fragmented forests. By extending the trait‐based response–effect framework toward the individual level, intraspecific variation in leaf economics traits can provide the missing functional link between environmental change and ecological processes. These findings suggest an important area for future research on incorporating ITV to understand and predict changes in ecosystem functioning in the context of global change.

Effect of straw return on soil respiration in dryland agroecosystem of China: A meta-analysis - Yanjun Zhang; Junliang Zou; Bruce Osborne; Wei Dang; Yuxia Xu; Yuanyuan Ren; Shuina Dang; Lijuan Wang; Xi Chen; Yuan Yu (Ecological Engineering, 2023)

A bispecific nanobody with high sensitivity/efficiency for simultaneous determination of carbaryl and its metabolite 1-naphthol in the soil and rice samples - Min-ling Liu; Zi-jian Chen; Xiao-qing Huang; Hong Wang; Jin-li Zhao; Yu-dong Shen; Lin Luo; Xiao-wei Wen; Bruce Hammock; Zhen-lin Xu (Environmental Pollution, 2023)

Precise isolation and structural origin of an ultra-specific nanobody against chemical compound - Huijuan Yang; Natalia Vasylieva; Jiaxin Wang; Zhenfeng Li; Wenbo Duan; Shuang Chen; Kai Wen; Hui Meng; Xuezhi Yu; Jianzhong Shen; Bruce D. Hammock; Zhanhui Wang (Journal of Hazardous Materials, 2023)

Correction: Preventive Pharmacovigilance: timely and precise prevention of adverse events through person-level patient screening and dose-level product surveillance - Yihua Bruce Yu; Katharine T. Briggs; Marc B. Taraban (Pharmaceutical Research, 2023)

Preventive Pharmacovigilance: timely and precise prevention of adverse events through person-level patient screening and dose-level product surveillance - Yihua Bruce Yu; Katharine T. Briggs; Marc B. Taraban (Pharmaceutical Research, 2023)
The goal of pharmacovigilance (PV) is to prevent adverse events (AEs) associated with drugs and vaccines. Current PV programs are of a reactive nature and rest entirely on data science, i.e., detecting and analyzing AE data from provider/patient reports, health records and even social media. The ensuing preventive actions are too late for people who have experienced AEs and often overly broad, as responses include entire product withdrawals, batch recalls, or contraindications of subpopulations. To prevent AEs in a timely and precise manner, it is necessary to go beyond data science and incorporate measurement science into PV efforts through person-level patient screening and dose-level product surveillance. Measurement-based PV may be called ‘preventive pharmacovigilance’, the goal of which is to identify susceptible individuals and defective doses to prevent AEs. A comprehensive PV program should contain both reactive and preventive components by integrating data science and measurement science.

Analysis of the Adsorbed Vaccine Formulations Using Water Proton Nuclear Magnetic Resonance—Comparison with Optical Analytics - Marc B. Taraban; Teresia Ndung’u; Pratima Karki; Kira Li; Ginny Fung; Marina Kirkitadze; Y. Bruce Yu (Pharmaceutical Research, 2023)

Assessing Antigen-Adjuvant Complex Stability Against Physical Stresses By wNMR - Marc B. Taraban; Katharine T. Briggs; Yihua Bruce Yu; Michael T. Jones; Lindsey Rosner; Akhilesh Bhambhani; Donna M. Williams; Christopher Farrell; Mikhail Reibarkh; Yongchao Su (Pharmaceutical Research, 2023)

Cardiac-specific overexpression of insulin-like growth factor II receptor-α interferes with the regulation of calcium homeostasis in the heart under hyperglycemic conditions - Shang-Yeh Lu; Bruce Chi-Kang Tsai; Dao Van Thao; Chin-Hu Lai; Michael Yu-Chih Chen; Wei-Wen Kuo; Chia-Hua Kuo; Kuan-Ho Lin; Dennis Jine-Yuan Hsieh; Chih-Yang Huang (Molecular Biology Reports, 2023)

A highly sensitive electrochemical immunosensor based on electrospun nanocomposite for the detection of parathion - Wen-jia Yin; Jing-xian Zhang; Hong Wang; Yu Wang; Xi Zeng; Zhen-lin Xu; Jin-yi Yang; Zhi-li Xiao; Bruce D. Hammock; Peng Wen (Food Chemistry, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The impact of climate change on global energy use - Hongliang Zhang; Jianhong E. Mu; Bruce A. McCarl; Jialing Yu (Mitigation and Adaptation Strategies for Global Change, 2022)

Excipient Innovation Through Precompetitive Research - Yihua Bruce Yu; Marc B. Taraban; Katharine T. Briggs; Robert G. Brinson; John P. Marino (Pharmaceutical Research, 2021)

Hyperglycemia-Induced Cardiac Damage Is Alleviated by Heat-Inactivated Lactobacillus reuteri GMNL-263 via Activation of the IGF1R Survival Pathway - Ker-Ping Koay; Bruce Chi-Kang Tsai; Chia-Hua Kuo; Wei-Wen Kuo; Hsiang-Ning Luk; Cecilia Hsuan Day; Ray-Jade Chen; Michael Yu-Chih Chen; V. Vijaya Padma; Chih-Yang Huang (Probiotics and Antimicrobial Proteins, 2021)

Heat-Killed Lactobacillus reuteri GMNL-263 Inhibits Systemic Lupus Erythematosus–Induced Cardiomyopathy in NZB/W F1 Mice - Yu-Lan Yeh; Min-Chi Lu; Bruce Chi-Kang Tsai; Bor-Show Tzang; Shiu-Min Cheng; Xiaoyong Zhang; Liang-Yo Yang; B. Mahalakshmi; Wei-Wen Kuo; Peng Xiang; Chih-Yang Huang (Probiotics and Antimicrobial Proteins, 2021)

Grand Challenges in Pharmaceutical Research Series: Ridding the Cold Chain for Biologics - Yihua Bruce Yu; Katharine T. Briggs; Marc B. Taraban; Robert G. Brinson; John P. Marino (Pharmaceutical Research, 2021)

Autotaxin stimulates LPA2 receptor in macrophages and exacerbates dextran sulfate sodium-induced acute colitis - Zi Wang; Wenjie Shi; Dean Tian; Hua Qin; Bruce A. Vallance; Hyungjun Yang; Hong B. Yu; Qin Yu (Journal of Molecular Medicine, 2020)

Characteristics of methane emissions in the Living Water Garden in Chengdu City from 2012 to 2017 - Ru Xue; Xiaoling Liu; Xiaoying Fu; Hongbing Luo; Ke Zhang; Bruce C. Anderson; Mei Li; Bo Huang; Lijuan Yu; Xiaoting Li; Shuzhi Fu; Aiping Pu; et al. (Environmental Science and Pollution Research, 2020)

Effect of diets on the feeding behavior and physiological properties of suspension-feeding sea cucumber Cucumaria frondosa - Zonghe Yu; Shawn Robinson; Bruce MacDonald; Terralynn Lander; Craig Smith (Journal of Oceanology and Limnology, 2020)

Soil carbon loss with warming: New evidence from carbon‐degrading enzymes - Ji Chen; Lars Elsgaard; Kees Jan van Groenigen; Jørgen E. Olesen; Zhi Liang; Yu Jiang; Poul E. Lærke; Yuefang Zhang; Yiqi Luo; Bruce A. Hungate; Robert L. Sinsabaugh; Uffe Jørgensen (Global Change Biology, 2020)
Climate warming affects soil carbon (C) dynamics, with possible serious consequences for soil C stocks and atmospheric CO 2 concentrations. However, the mechanisms underlying changes in soil C storage are not well understood, hampering long‐term predictions of climate C‐feedbacks. The activity of the extracellular enzymes ligninase and cellulase can be used to track changes in the predominant C sources of soil microbes and can thus provide mechanistic insights into soil C loss pathways. Here we show, using meta‐analysis, that reductions in soil C stocks with warming are associated with increased ratios of ligninase to cellulase activity. Furthermore, whereas long‐term (≥5 years) warming reduced the soil recalcitrant C pool by 14%, short‐term warming had no significant effect. Together, these results suggest that warming stimulates microbial utilization of recalcitrant C pools, possibly exacerbating long‐term climate‐C feedbacks.

Lower‐than‐expected CH 4 emissions from rice paddies with rising CO 2 concentrations - Haoyu Qian; Shan Huang; Jin Chen; Ling Wang; Bruce A. Hungate; Chris van Kessel; Jun Zhang; Aixing Deng; Yu Jiang; Kees Jan van Groenigen; Weijian Zhang (Global Change Biology, 2020)
Elevated atmospheric CO 2 (eCO 2 ) generally increases carbon input in rice paddy soils and stimulates the growth of methane‐producing microorganisms. Therefore, eCO 2 is widely expected to increase methane (CH 4 ) emissions from rice agriculture, a major source of anthropogenic CH 4 . Agricultural practices strongly affect CH 4 emissions from rice paddies as well, but whether these practices modulate effects of eCO 2 is unclear. Here we show, by combining a series of experiments and meta‐analyses, that whereas eCO 2 strongly increased CH 4 emissions from paddies without straw incorporation, it tended to reduce CH 4 emissions from paddy soils with straw incorporation. Our experiments also identified the microbial processes underlying these results: eCO 2 increased methane‐consuming microorganisms more strongly in soils with straw incorporation than in soils without straw, with the opposite pattern for methane‐producing microorganisms. Accounting for the interaction between CO 2 and straw management, we estimate that eCO 2 increases global CH 4 emissions from rice paddies by 3.7%, an order of magnitude lower than previous estimates. Our results suggest that the effect of eCO 2 on CH 4 emissions from rice paddies is smaller than previously thought and underline the need for judicious agricultural management to curb future CH 4 emissions.

Mode of silver clearance following 28-day inhalation exposure to silver nanoparticles determined from lung burden assessment including post-exposure observation periods - Mi Seong Jo; Jin Kwon Kim; Younghun Kim; Hoi Pin Kim; Hee Sang Kim; Kangho Ahn; Ji Hyun Lee; Elaine M. Faustman; Mary Gulumian; Bruce Kelman; Il Je Yu (Archives of Toxicology, 2020)

Global in situ Observations of Essential Climate and Ocean Variables at the Air–Sea Interface - Luca R. Centurioni; Jon Turton; Rick Lumpkin; Lancelot Braasch; Gary Brassington; Yi Chao; Etienne Charpentier; Zhaohui Chen; Gary Corlett; Kathleen Dohan; Craig Donlon; Champika Gallage; et al. (Frontiers in Marine Science, 2019)

Bismuth Subsalicylate Coagulopathy in a Patient with Chronic Liver Disease - Catherine Yu; Noel Eustaquio; Diane P. Calello; Bruce E. Ruck; Lewis S. Nelson; Cynthia Santos (Journal of Medical Toxicology, 2019)

Correction to: Nondestructive Quantitative Inspection of Drug Products Using Benchtop NMR Relaxometry—the Case of NovoMix® 30 - Katharine T. Briggs; Marc B. Taraban; Weizhen Wang; Y. Bruce Yu (AAPS PharmSciTech, 2019)

Nondestructive Quantitative Inspection of Drug Products Using Benchtop NMR Relaxometry—the Case of NovoMix® 30 - Katharine T. Briggs; Marc B. Taraban; Weizhen Wang; Y. Bruce Yu (AAPS PharmSciTech, 2019)

Generation of a selectable marker free, highly expressed single copy locus as landing pad for transgene stacking in sugarcane - Yang Zhao; Jae Y. Kim; Ratna Karan; Je H. Jung; Bhuvan Pathak; Bruce Williamson; Baskaran Kannan; Duoduo Wang; Chunyang Fan; Wenjin Yu; Shujie Dong; Vibha Srivastava; et al. (Plant Molecular Biology, 2019)

Limited potential of harvest index improvement to reduce methane emissions from rice paddies - Yu Jiang; Haoyu Qian; Ling Wang; Jinfei Feng; Shan Huang; Bruce A. Hungate; Chris van Kessel; William R. Horwath; Xingyue Zhang; Xiaobo Qin; Yue Li; Xiaomin Feng; et al. (Global Change Biology, 2019)
Rice is a staple food for nearly half of the world's population, but rice paddies constitute a major source of anthropogenic CH 4 emissions. Root exudates from growing rice plants are an important substrate for methane‐producing microorganisms. Therefore, breeding efforts optimizing rice plant photosynthate allocation to grains, i.e., increasing harvest index (HI), are widely expected to reduce CH 4 emissions with higher yield. Here we show, by combining a series of experiments, meta‐analyses and an expert survey, that the potential of CH 4 mitigation from rice paddies through HI improvement is in fact small. Whereas HI improvement reduced CH 4 emissions under continuously flooded (CF) irrigation, it did not affect CH 4 emissions in systems with intermittent irrigation (II). We estimate that future plant breeding efforts aimed at HI improvement to the theoretical maximum value will reduce CH 4 emissions in CF systems by 4.4%. However, CF systems currently make up only a small fraction of the total rice growing area (i.e., 27% of the Chinese rice paddy area). Thus, to achieve substantial CH 4 mitigation from rice agriculture, alternative plant breeding strategies may be needed, along with alternative management.

Intermittent micro-aeration control of methane emissions from an integrated vertical-flow constructed wetland during agricultural domestic wastewater treatment - Xiaoling Liu; Ke Zhang; Liangqian Fan; Hongbing Luo; Mingshu Jiang; Bruce C. Anderson; Mei Li; Bo Huang; Lijuan Yu; Guozhu He; Jingting Wang; Aiping Pu (Environmental Science and Pollution Research, 2018)

Metabarcoding of freshwater invertebrates to detect the effects of a pesticide spill - Carmelo Andújar; Paula Arribas; Clare Gray; Catherine Bruce; Guy Woodward; Douglas W. Yu; Alfried P. Vogler (Molecular Ecology, 2018)
Biomonitoring underpins the environmental assessment of freshwater ecosystems and guides management and conservation. Current methodology for surveys of (macro)invertebrates uses coarse taxonomic identification where species‐level resolution is difficult to obtain. Next‐generation sequencing of entire assemblages (metabarcoding) provides a new approach for species detection, but requires further validation. We used metabarcoding of invertebrate assemblages with two fragments of the cox1 “barcode” and partial nuclear ribosomal ( SSU ) genes, to assess the effects of a pesticide spill in the River Kennet (southern England). Operational taxonomic unit ( OTU ) recovery was tested under 72 parameters (read denoising, filtering, pair merging and clustering). Similar taxonomic profiles were obtained under a broad range of parameters. The SSU marker recovered Platyhelminthes and Nematoda, missed by cox1 , while Rotifera were only amplified with cox1 . A reference set was created from all available barcode entries for Arthropoda in the BOLD database and clustered into OTU s. The River Kennet metabarcoding produced matches to 207 of these reference OTU s, five times the number of species recognized with morphological monitoring. The increase was due to the following: greater taxonomic resolution (e.g., splitting a single morphotaxon “Chironomidae” into 55 named OTU s); splitting of Linnaean binomials into multiple molecular OTU s; and the use of a filtration‐flotation protocol for extraction of minute specimens (meiofauna). Community analyses revealed strong differences between “impacted” vs. “control” samples, detectable with each gene marker, for each major taxonomic group, and for meio‐ and macrofaunal samples separately. Thus, highly resolved taxonomic data can be extracted at a fraction of the time and cost of traditional nonmolecular methods, opening new avenues for freshwater invertebrate biodiversity monitoring and molecular ecology.

Relationships between typhoons, climate and crime rates in Taiwan - Chin-Hsien Yu; Jianhong E. Mu; Jinxiu Ding; Bruce A. McCarl (Natural Hazards, 2017)

Competition for electrons between pyridine and quinoline during their simultaneous biodegradation - Hua Xu; Weihua Sun; Ning Yan; Danni Li; Xueqi Wang; Tingting Yu; Yongming Zhang; Bruce E. Rittmann (Environmental Science and Pollution Research, 2017)

Higher yields and lower methane emissions with new rice cultivars - Yu Jiang; Kees Jan van Groenigen; Shan Huang; Bruce A. Hungate; Chris van Kessel; Shuijin Hu; Jun Zhang; Lianhai Wu; Xiaojun Yan; Lili Wang; Jin Chen; Xiaoning Hang; et al. (Global Change Biology, 2017)
Breeding high‐yielding rice cultivars through increasing biomass is a key strategy to meet rising global food demands. Yet, increasing rice growth can stimulate methane ( CH 4 ) emissions, exacerbating global climate change, as rice cultivation is a major source of this powerful greenhouse gas. Here, we show in a series of experiments that high‐yielding rice cultivars actually reduce CH 4 emissions from typical paddy soils. Averaged across 33 rice cultivars, a biomass increase of 10% resulted in a 10.3% decrease in CH 4 emissions in a soil with a high carbon (C) content. Compared to a low‐yielding cultivar, a high‐yielding cultivar significantly increased root porosity and the abundance of methane‐consuming microorganisms, suggesting that the larger and more porous root systems of high‐yielding cultivars facilitated CH 4 oxidation by promoting O 2 transport to soils. Our results were further supported by a meta‐analysis, showing that high‐yielding rice cultivars strongly decrease CH 4 emissions from paddy soils with high organic C contents. Based on our results, increasing rice biomass by 10% could reduce annual CH 4 emissions from Chinese rice agriculture by 7.1%. Our findings suggest that modern rice breeding strategies for high‐yielding cultivars can substantially mitigate paddy CH 4 emission in China and other rice growing regions.

Genetic Variants of Microtubule Actin Cross-linking Factor 1 (MACF1) Confer Risk for Parkinson’s Disease - Xin Wang; Nuomin Li; Nian Xiong; Qi You; Jie Li; Jinlong Yu; Hong Qing; Tao Wang; Heather J. Cordell; Ole Isacson; Jeffery M. Vance; Eden R. Martin; et al. (Molecular Neurobiology, 2017)

Advancing Product Quality: a Summary of the Second FDA/PQRI Conference - Lawrence X. Yu; Ilgaz Akseli; Barbara Allen; Gregory Amidon; Tara Gooen Bizjak; Ashley Boam; Margaret Caulk; David Doleski; Joseph Famulare; Adam C. Fisher; Scott Furness; Brian Hasselbalch; et al. (The AAPS Journal, 2016)

Tungsten Carbide-Cobalt Nanoparticles Induce Reactive Oxygen Species, AKT, ERK, AP-1, NF-κB, VEGF, and Angiogenesis - Ling-Zhi Liu; Min Ding; Jenny Z. Zheng; Yingxue Zhu; Bruce A. Fenderson; Bingyun Li; Jing J. Yu; Bing-Hua Jiang (Biological Trace Element Research, 2015)

Association between tobacco use and the upper gastrointestinal microbiome among Chinese men - Emily Vogtmann; Roberto Flores; Guoqin Yu; Neal D. Freedman; Jianxin Shi; Mitchell H. Gail; Bruce A. Dye; Guo-Qing Wang; Vanja Klepac-Ceraj; Bruce J. Paster; Wen-Qiang Wei; Hui-Qin Guo; et al. (Cancer Causes & Control, 2015)

Beauveria bassiana sensu lato granules for management of brown planthopper, Nilaparvata lugens in rice - Se Jin Lee; Jeong Seon Yu; Yu-Shin Nai; Bruce L. Parker; Margaret Skinner; Jae Su Kim (BioControl, 2015)

Enhanced diversity and aflatoxigenicity in interspecific hybrids of Aspergillus flavus and Aspergillus parasiticus - Rodrigo A. Olarte; Carolyn J. Worthington; Bruce W. Horn; Geromy G. Moore; Rakhi Singh; James T. Monacell; Joe W. Dorner; Eric A. Stone; De‐Yu Xie; Ignazio Carbone (Molecular Ecology, 2015)
Aspergillus flavus and A. parasiticus are the two most important aflatoxin‐producing fungi responsible for the contamination of agricultural commodities worldwide. Both species are heterothallic and undergo sexual reproduction in laboratory crosses. Here we examine the possibility of interspecific matings between A. flavus and A. parasiticus . These species can be distinguished morphologically and genetically, as well as by their mycotoxin profiles. Aspergillus flavus produces both B aflatoxins and cyclopiazonic acid ( CPA ), B aflatoxins or CPA alone, or neither mycotoxin; Aspergillus parasiticus produces B and G aflatoxins or the aflatoxin precursor O ‐methylsterigmatocystin, but not CPA . Only four of forty‐five attempted interspecific crosses between opposite mating types of A. flavus and A. parasiticus were fertile and produced viable ascospores. Single ascospore strains from each cross were shown to be recombinant hybrids using multilocus genotyping and array comparative genome hybridization. Conidia of parents and their hybrid progeny were haploid and predominantly monokaryons and dikaryons based on flow cytometry. Multilocus phylogenetic inference showed that experimental hybrid progeny were grouped with naturally occurring A. flavus L strain and A. parasiticus . Higher total aflatoxin concentrations in some F1 progeny strains compared to midpoint parent aflatoxin levels indicate synergism in aflatoxin production; moreover, three progeny strains synthesized G aflatoxins that were not produced by the parents, and there was evidence of allopolyploidization in one strain. These results suggest that hybridization is an important diversifying force resulting in the genesis of novel toxin profiles in these agriculturally important fungi.

Reliable, verifiable and efficient monitoring of biodiversity via metabarcoding - Yinqiu Ji; Louise Ashton; Scott M. Pedley; David P. Edwards; Yong Tang; Akihiro Nakamura; Roger Kitching; Paul M. Dolman; Paul Woodcock; Felicity A. Edwards; Trond H. Larsen; Wayne W. Hsu; et al. (Ecology Letters, 2013)
To manage and conserve biodiversity, one must know what is being lost, where, and why, as well as which remedies are likely to be most effective. Metabarcoding technology can characterise the species compositions of mass samples of eukaryotes or of environmental DNA . Here, we validate metabarcoding by testing it against three high‐quality standard data sets that were collected in Malaysia (tropical), China (subtropical) and the United Kingdom (temperate) and that comprised 55,813 arthropod and bird specimens identified to species level with the expenditure of 2,505 person‐hours of taxonomic expertise. The metabarcode and standard data sets exhibit statistically correlated alpha‐ and beta‐diversities, and the two data sets produce similar policy conclusions for two conservation applications: restoration ecology and systematic conservation planning. Compared with standard biodiversity data sets, metabarcoded samples are taxonomically more comprehensive, many times quicker to produce, less reliant on taxonomic expertise and auditable by third parties, which is essential for dispute resolution.

Repeat oral dose toxicity studies of melamine in rats and monkeys - Richard J. Early; Hong Yu; Xueyan Peter Mu; Haiyan Xu; Lei Guo; Qingxue Kong; Junma Zhou; Bruce He; Xiuying Yang; Hailiang Huang; Edward Hu; Ying Jiang (Archives of Toxicology, 2013)

An fMRI Study of the Differences in Brain Activity During Active Ankle Dorsiflexion and Plantarflexion - Jonathan P. Trinastic; Steven A. Kautz; Keith McGregor; Chris Gregory; Mark Bowden; Michelle B. Benjamin; Marc Kurtzman; Yu Ling Chang; Tim Conway; Bruce Crosson (Brain Imaging and Behavior, 2010)

Concordance and Discordance Between Brain Perfusion and Atrophy in Frontotemporal Dementia - Soichiro Shimizu; Yu Zhang; Joel Laxamana; Bruce L. Miller; Joel H. Kramer; Michael W. Weiner; Norbert Schuff (Brain Imaging and Behavior, 2010)

Delivered Dose: A Drug-centric Phenotype for Chemotherapy Dose Individualization - Y. Bruce Yu (Pharmaceutical Research, 2009)

Numerical issues in computing inundation areas over natural terrains using Savage-Hutter theory - Bin Yu; Keith Dalbey; Amy Webb; Marcus Bursik; Abani Patra; E. Bruce Pitman; Camil Nichita (Natural Hazards, 2009)

Number of aberrant crypt foci associated with adiposity and IGF1 bioavailability - Helen Swede; Thomas E. Rohan; Herbert Yu; Joseph C. Anderson; Richard G. Stevens; Jane Brokaw; Joel Levine; Bruce M. Brenner; Carl D. Malchoff; Valerie B. Duffy; Devon C. Pleau; Daniel W. Rosenberg (Cancer Causes & Control, 2009)

Assessing the impact of socio-economic status on cancer survival in New South Wales, Australia 1996–2001 - Xue Qin Yu; Dianne L. O’Connell; Robert W. Gibberd; Bruce K. Armstrong (Cancer Causes & Control, 2008)

Ethnobotanical ground‐truthing: indigenous knowledge, floristic inventories and satellite imagery in the upper Rio Negro, Brazil - Marcia Barbosa Abraão; Bruce W. Nelson; João Cláudio Baniwa; Douglas W. Yu; Glenn H. Shepard Jr (Journal of Biogeography, 2008)
Aim To assess the utility of indigenous habitat knowledge in studies of habitat diversity in Amazonia. Location Baniwa indigenous communities in Rio Içana, upper Rio Negro, Brazil. Methods Six campinarana vegetation types, recognized and named by a consensus of Baniwa indigenous informants according to salient indicator species, were studied in 15 widely distributed plots. Floristic composition (using Baniwa plant nomenclature only, after frustrated attempts to obtain botanical collection permits), quantitative measures of forest structure and GPS waypoints of the 4‐ha composite plot contours were registered, permitting their location on Landsat satellite images. Non‐metric multidimensional scaling (NMDS) ordination was carried out using pc‐ord software. Results The NMDS ordinations of the plot data revealed a clear gradient of floristic composition that was highly correlated with three quantitative measures of forest structure: basal area, canopy height and satellite reflectance. Main conclusions Baniwa‐defined forest types are excellent predictors of habitat diversity along the structural gradient comprising distinctive white‐sand campinarana vegetation types. Indigenous ecological knowledge, as revealed by satellite imagery and floristic analyses, proves to be a powerful and efficient shortcut to assessing habitat diversity, promoting dialogue between scientific and indigenous worldviews, and promoting joint study and conservation of biodiversity.

Critical role of phosphoinositide 3-kinase cascade in adipogenesis of human mesenchymal stem cells - Weihua Yu; Zhenguang Chen; Jinli Zhang; Lirong Zhang; Hui Ke; Lihua Huang; Yanwen Peng; Xiuming Zhang; Shunong Li; Bruce T. Lahn; Andy Peng Xiang (Molecular and Cellular Biochemistry, 2008)

Proteomic identification of differently expressed proteins responsible for osteoblast differentiation from human mesenchymal stem cells - Ai-Xia Zhang; Wei-Hua Yu; Bao-Feng Ma; Xin-Bing Yu; Frank Fuxiang Mao; Wei Liu; Jia-Qing Zhang; Xiu-Ming Zhang; Shu-Nong Li; Ming-Tao Li; Bruce T. Lahn; Andy Peng Xiang (Molecular and Cellular Biochemistry, 2007)

Functional MRI of Language in Aphasia: A Review of the Literature and the Methodological Challenges - Bruce Crosson; Keith McGregor; Kaundinya S. Gopinath; Tim W. Conway; Michelle Benjamin; Yu-Ling Chang; Anna Bacon Moore; Anastasia M. Raymer; Richard W. Briggs; Megan G. Sherod; Christina E. Wierenga; Keith D. White (Neuropsychology Review, 2007)

Estimating Regional Variation in Cancer Survival: A Tool for Improving Cancer Care - Xue Q. Yu; Dianne L. O'Connell; Robert W. Gibberd; David P. Smith; Paul W. Dickman; Bruce K. Armstrong (Cancer Causes & Control, 2004)

A two-step model for the kinetics of BTX degradation and intermediate formation by Pseudomonas putida F1 - Haibo Yu; Byung J. Kim; Bruce E. Rittmann (Biodegradation, 2001)

The roles of intermediates in biodegradation of benzene, toluene, and p-xylene by Pseudomonas putida F1 - Haibo Yu; Byung J. Kim; Bruce E. Rittmann (Biodegradation, 2001)

Spectral Properties of Single BODIPY Dyes in Polystyrene Microspheres and in Solutions - Bruce P. Wittmershaus; Jamie J. Skibicki; Jason B. McLafferty; Yu-Zhong Zhang; Sharon Swan (Journal of Fluorescence, 2001)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)